The International Drug Control Conventions - United Nations Office on Drugs; Crime (United Nations, 2013)
The present publication contains the texts of the three main international drug control conventions: the Single Convention on Narcotic Drugs of 1961 as amended by the 1972 Protocol; the Convention on Psychotropic Substances of 1971; and the United Nations Convention against Illicit Traffic in Narcotic Drugs and Psychotropic Substances of 1988. Annex I contains a table showing the year in which the narcotic drugs and psychotropic substances were placed under international control. Annex II shows the year in which substances frequently used in the illicit manufacture of narcotic drugs and psychotropic substances were placed under the control of the 1988 Convention.